Immobilization of Hyperthermostable β amylase from Bacillus Subtilis DJ5 into gelatin film by Glutaraldehyde Crosslinking. - ABHIJIT PODDAR; SUBHAS CHANDRA JANA (International Journal of Pharma and Bio Sciences, 2011)
β amylase isolated from Bacillus subtilis DJ5 were immobilized covalently in 5% and 10% gelatin matrix using glutaraldehyde as crosslinking agent. Initial screening proved enzyme immobilized in 10% gelatin with 0.8% glutaraldehyde gave higher catalytic activity (3.33 U/ml) and immobilization efficiency (88%) after 18 hour of crosslinkage at 4 °C. Moreover this matrix can be used repeatedly seven times retaining 41% enzymatic activity (1.37 U/ml) at 7th cycle. Immobilized matrix showed greater stability in presence of detergents and inhibitors compared with free enzyme system. Enzymatic activity was not compromised at any level of immobilization as both immobilized and free enzyme required same concentration of substrate (5mg/ml). But higher catalytic activity of immobilized enzyme (2.95 U/ml) than free enzyme (2.47 U/ml) indicated immobilized matrix allowed proper orientation of enzyme substrate in reaction microenvironment. Suitability of immobilized β amylase will make it more acceptable from industrial point of view